AB1202 The Country Where You Perform Your Rheumatology Training is Associated with the Acquired Confidence, The Education Received and the Assessments in Core Competences. (9th June 2015) - Sivera, F.; Ramiro, S.; Cikes, N.; Dougados, M.; Gossec, L.; Kvien, T.K.; Lundberg, I.E.; Mandl, P.; Moorthy, A.; Panchal, S.; da Silva, J.A.; Bijlsma, J.W.
Abstract : Objectives: To assess the association between the country where rheumatology training takes place and the acquired confidence, exposure to education, practical experience and competence assessments in 21 core competences Methods: As part of a European project to evaluate the differences in training in rheumatology across Europe, we developed an online survey to assess the training experience. The target population was rheumatologytrainees and rheumatologists certified in the past 5 years. We selected 21 competences, core to rheumatology: 13 clinical (MSK examination, detecting synovitis, managing a patient with monoarthritis, lab test interpretation, managing a patient with OA, gout, early RA/undifferentiated arthritis, SpA, CTD, vasculitis, OP, with a biologic DMARD, using disease activity measures), 4 procedures (knee arthrocentesis, crystal identification, hand X-ray interpretation, performing an MSK US) and 4 generic competences (engaging in a multidisciplinary team, interpreting a research paper, performing a scientific presentation, and patient communication). For each competence, respondents were asked to assess the confidence in their abilities (0-10), the exposure to formal education (yes/no), the amount of patient experience (0; 1-10; 11-50; 51-100; 101-150; >150) and assessment (yes/no) where appropriate. For each competence, regression models (linear or logistic, as appropriate) were developed to assess the influence of country of training on the level of confidence, education, practical experience and assessment for that given competence. Results: 1243 answers were included in the analysis (30% male, 58% trainees) from the 41 EULAR countries that offer rheumatology post-graduate training. For all given competences, the country of training was significantly associated with the acquired confidence. For example, trainees from the UK (arbitrary reference) had on average 1.4 points higher confidence in their ability to manage a patient with early RA than a trainee from France (Table 1 ). Education and exposure to ≥10 patients were also associated with the acquired confidence for all competences. The existence of an assessment was associated to the level of confidence for only some competences (MSK exam, managing a patient with CTD, with vasculitis, crystal ID, MSK US, multidisciplinary team and interpreting a paper). The country of training was also associated with a higher odds of receiving formal education, of being exposed to ≥10 patients and of being assessed in a given competence (all separate multivariable models). Conclusions: The European country where rheumatology postgraduate training is performed is associated with the level of confidence acquired in many of the core competences, odds of receiving formal education, of patient experience and of assessment. Further attempts are needed to harmonize rheumatology training educational outcomes across Europe. Disclosure of Interest: None declared